2012
DOI: 10.1371/journal.pone.0049133
|View full text |Cite
|
Sign up to set email alerts
|

IL12RB2 Gene Is Associated with the Age of Type 1 Diabetes Onset in Croatian Family Trios

Abstract: BackgroundCommon complex diseases are influenced by both genetic and environmental factors. Many genetic factors overlap between various autoimmune diseases. The aim of the present study is to determine whether four genetic variants known to be risk variants for several autoimmune diseases could be associated with an increased susceptibility to type 1 diabetes mellitus.Methods and FindingsWe genotyped four genetic variants (rs2358817, rs1049550, rs6679356, rs9865818) within VTCN1, ANXA11, IL12RB2 and LPP genes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 28 publications
(35 reference statements)
2
3
0
Order By: Relevance
“…4d,e). These findings, along with other similar studies [38][39][40][41], suggest the presence of a more prominent proinflammatory profile of immune cells in children with a younger age at onset of T1D than those diagnosed at older ages. In addition, our previous study suggests that the timing by which immunological markers are investigated following the onset of T1D is critical in understanding disease development [42].…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…4d,e). These findings, along with other similar studies [38][39][40][41], suggest the presence of a more prominent proinflammatory profile of immune cells in children with a younger age at onset of T1D than those diagnosed at older ages. In addition, our previous study suggests that the timing by which immunological markers are investigated following the onset of T1D is critical in understanding disease development [42].…”
Section: Discussionsupporting
confidence: 84%
“…However, older children had higher values of slan -CD16 -mDC and non-activated (HLA-DR -CD38 -) CD4 + and CD8 + T cells compared to younger children (Fig. These findings, along with other similar studies [38][39][40][41], suggest the presence of a more prominent proinflammatory profile of immune cells in children with a younger age at onset of T1D than those diagnosed at older ages. 4d,e).…”
Section: Discussionsupporting
confidence: 69%
“…The prevalence of T1DM accounts for 5-10% of all diabetes cases (Gale, 2002;Awoniyi et al, 2013;Lipman et al, 2013). Although the exact pathogenesis of T1DM is unknown, T1DM is thought to involve multifactor disorders resulting from genetic polymorphisms as well as various environmental factors (Rich et al, 2006;Ei Wafai et al, 2011;Pehlić et al, 2012;Hadžija et al, 2013). Previous studies have indicated that genetic polymorphisms in genes such as TRAIL (Bernardi et al, 2012), HLA (Black and Dabelea, 2013), and CCR5 (Yang et al, 2004) were associated with T1DM risk.…”
Section: Introductionmentioning
confidence: 99%
“…The co-occurrence of juvenile idiopathic arthritis and type 1 diabetes mellitus is known and has been previously described [ 4 , 6 9 ]. In our patient, symptoms of type 1 diabetes mellitus occurred after the recognition of juvenile idiopathic arthritis.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous genetic studies have demonstrated more than fifty susceptibility genes, which indicate the possibility of co-occurrence of autoimmune diseases including connective tissue diseases and the digestive system diseases with celiac disease [ 9 ].…”
Section: Discussionmentioning
confidence: 99%